2015
DOI: 10.1039/c5lc00254k
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic optofluidic ring resonator lasers created by femtosecond laser nanofabrication

Abstract: We designed, fabricated, and characterized a monolithically integrated optofluidic ring resonator laser that is mechanically, thermally, and chemically robust. The entire device, including the ring resonator channel and sample delivery microfluidics, was created in a block of fused-silica glass using a 3-dimensional femtosecond laser writing process. The gain medium, composed of Rhodamine 6G (R6G) dissolved in quinoline, was flowed through the ring resonator. Lasing was achieved at a pump threshold of approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 43 publications
(70 reference statements)
0
25
0
Order By: Relevance
“…The whispering gallery mode (WGM) laser cavities can be constructed in the form of solid cylinders, circular‐shaped capillaries, microspheres, microdroplets, microdisks, ring‐shaped waveguides, and rectangular shaped rods . The WGM cavity relies on the total internal reflection at the curved boundary to provide optical feedback.…”
Section: Biological and Biomedical Sensingmentioning
confidence: 99%
“…The whispering gallery mode (WGM) laser cavities can be constructed in the form of solid cylinders, circular‐shaped capillaries, microspheres, microdroplets, microdisks, ring‐shaped waveguides, and rectangular shaped rods . The WGM cavity relies on the total internal reflection at the curved boundary to provide optical feedback.…”
Section: Biological and Biomedical Sensingmentioning
confidence: 99%
“…Since Garrett et al demonstrated the first WGM lasers in 1961 2 , WGM microresonators have been widely used in the field of microlasers because of the high Q factor and the small mode volumes 8,25,53,[61][62][63][64] . Due to these advantages, microlasers based on WGM microresonators can obtain an ultralow lasing threshold.…”
Section: Microlasersmentioning
confidence: 99%
“…In 2015 the design, fabrication, and characterization of a monolithically integrated optofluidic ring resonator using FMT has been reported [16].…”
Section: Previous Resonator Designsmentioning
confidence: 99%
“…In the next section we will briefly review: the first demonstration of an optofluidic resonator realized by FMT given more than a decade ago [15] and a recently reported optofluidic ring resonator fabricated by femtosecond laser nanofabrication in two glass substrates melted together as post-process [16]. In the third section we will summarize our recent results by coupling FMT with high resolution ink-jet printing to realize low threshold Fabry-Perot resonators in monolithic microfluidic platforms…”
Section: Introductionmentioning
confidence: 99%